Analisis Laporan Keuangan sebagai Alat untuk Menilai Kinerja Keuangan Perusahaan pada PT. Pembangunan Perumahan (Persero) Tbk - Nadhila Nuraini; Dalizanolo Hulu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The objective of this study is to evaluate the financial performance of PT PP (Persero) Tbk over the period from 2020 to 2023. The assessment was conducted by analyzing several key financial ratios, including profitability, liquidity, solvency, and activity ratios. This study employed a descriptive quantitative approach using secondary data obtained from the company’s annual financial statements. The analysis revealed a decline in the company’s profitability, as indicated by a downward trend in the Return on Assets (ROA) and Return on Equity (ROE) ratios. The company's liquidity remained relatively stable but was still below the ideal standard, particularly in the quick ratio, indicating a need for improvement in the management of liquid assets. The solvency analysis revealed a high dependency on debt, which could increase financial risk if not properly managed. Meanwhile, the activity ratios showed a decrease in operational efficiency in utilizing assets to generate revenue. These findings support the hypothesis that PT PP (Persero) Tbk is facing challenges in maintaining financial health, particularly in balancing growth with sustainable performance. This study has limitations, including a data scope restricted to financial ratios and the absence of consideration for external factors such as macroeconomic conditions and industry comparisons. Future research is recommended to adopt a more comprehensive and integrative approach by combining quantitative and qualitative methods, in order to gain deeper insights into financial decision-making processes and the company’s strategic direction.